Synthesis of niobium substituted cobalt-nickel nano-ferrite (Co0.5Ni0.5NbxFe2-xO4 (x ≤ 0.1) by hydrothermal approach show strong anti-colon cancer activities. Issue 6 (31st March 2021) - Tombuloglu, H.; Khan, F.A.; Almessiere, M.A.; Aldakheel, S.; Baykal, A.
Abstract: The combination of two or more nanoparticles found to be effective strategy to synthesize nanocomposites for better drug delivery and treatment. In the present study, we have combined cobalt (Co), nickel (Ni), niobium (Nb), and iron oxide (Fe2 O4 ) and prepared niobium substituted cobalt-nickel nano-ferrite nanocomposites (Co0.5 Ni0.5 Nbx Fe2-x O4 ( x ≤ 0.1) by using hydrothermal approach. We have characterized the structure and morphology of nanocomposites by using XRD, EDX, TEM and SEM methodologies. We have examined the impact of nanocomposites (Co0.5 Ni0.5 Nbx Fe2-x O4 ( x ≤ 0.1) on cancerous cells (human colorectal carcinoma cells, HCT-116) by using MTT assay. We have also checked the impact of nanocomposites on normal and non-cancerous cells (human embryonic kidney cells, HEK-293) to confirm the specificity of their actions. Post- 48 h treatment of Co0.5 Ni0.5 Nbx Fe2-x O4 ( x ≤ 0.1) led to dose-dependent inhibition of cancer cells growth and proliferation. However, no cytotoxic effect was observed on the normal cells (HEK-293). In addition, DAPI stained nuclear DNA staining analysis demonstrates that the Co0.5 Ni0.5 Nbx Fe2-x O4 ( x ≤ 0.1) treatment also caused nuclear DNA disintegration which is the marker for programmed cell death. These results demonstrate that synthesized nanocomposites Co0.5 Ni0.5 Nbx Fe2-x O4 ( x ≤ 0.1) selectively target the colon cancer cells and induce cancer cell death. Communicated by Ramaswamy H. Sarma